Consultation and consent under the MPRDA and the IPILRA: a legal analysis of the decision-making practices of customary communities in South Africa - Ntsanwisi, Fezeka (Private Law, 2022)
Under the Mineral and Petroleum Resources Development Act 28 of 2002 (MPRDA), the State, as custodian of mineral resources, has the authority to grant rights to minerals and permits in favour of applicants that satisfy the requirements of the prescribed application procedures. Applicants for rights to minerals and permits must consult meaningfully with landowners and lawful occupiers, although the MPRDA itself does not require the latter's prior consent. The Interim Protection of Informal Land Rights Act 31 of 1996 (IPILRA), by contrast, requires prior consent when persons are deprived of their informal rights to land. In South Africa, communities that occupy land under customary land tenure are recognised as lawful occupiers that have informal rights to land. The occupation of land by customary communities and the applicant's interest to exploit mineral resources creates competing rights and interests between these two parties, namely: a right to consultation and a right of access to land. This minor dissertation aims to analyse the impact that the current statutory formulation of the requirements of consultation and consent has on the informal rights to land held by customary communities. This aim translates into two sub-inquiries: How do the statutorily required processes of consultation and consent embodied in the MPRDA and the IPILRA protect the informal rights to land held by customary communities? Furthermore, do the statutorily required processes of consultation and consent meaningfully engage with the existing decision-making practices of customary communities? These issues are considered in light of the elevated status that customary law enjoys under South African law and the Constitution's aspiration to reform racially discriminatory landholding systems. The dissertation argues that the statutorily required processes of consultation and consent inadequately engage with the existing decision-making practices of customary communities. It offers insight on how engagement with the existing decision-making practices, and with the Free, Prior and Informed Consent principle, can better accommodate and protect the rights and interests of customary communities that are affected by prospecting and mining operations.